A case study of congenital adrenal hyperplasia - Kamat, Raksha; Chaudhary, Upendra; Trivedi, Sangita (Indian Journal of Child Health, 2024)
Congenital adrenal hyperplasia (CAH) is a rare condition with a variety of symptoms. The most serious “salt losing” scenario is a medical emergency. A lack of 21 a-hydroxylase causes more than 90% of cases of CAH (21aOH). The adrenals produce excess sex hormones rather than cortisol. The vast majority of patients are unable to produce enough aldosterone. Girls are virilized, there is rapid somatic growth with the early epiphyseal fusion in both sexes, and there is even life-threatening hyponatremic dehydration. The following case report evaluates the clinical features, signs, and symptoms of CAH. A 1-day-old baby was admitted to the Neonatal Intensive Care Unit at the Department of Pediatrics, New Civil Hospital, Surat, for ambiguous genitalia. Various studies were conducted, and karyotyping suggestive of 46xx 17OH progesterone decreased. The sodium level was 114.64 mmol and the potassium level was 4.81 mmol on electrolyte analysis. CAH is an autosomal recessive disorder, in which 21-hydroxylase deficiency is the most common cause. In children, hydrocortisone is the preferred treatment.